RE-EXAMINATION OF THE DETERMINATION OF LABOR SERVICE SUPERVISORS REVIEW FROM THE PERSPECTIVE OF LAW NO. 30 YEAR 2014 - Thamrin, Husni; Nason Nadeak (Awang Long Law Review, 2021)
The re-examination of the determination of the Provincial Labor Inspector as regulated in article 28 paragraph 3 of the Regulation of the Minister of Manpower of the Republic of Indonesia No.33 of 2016, which has been changed to Regulation of the Minister of Manpower of the Republic of Indonesia 1 of 2020, is legally no longer valid. Apart from being based on Law no. 30 of 2014, there are also several legal references as the basis for rejecting the re-examination of the determination as regulated in Article 28 of the Regulation of the Minister of Manpower of the Republic of Indonesia No. 33 of 2016, which has been changed to Regulation of the Minister of Manpower of the Republic of Indonesia No. 1 year 2020.